2018
DOI: 10.25165/j.ijabe.20181103.3942
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of soil nutrients and their relationship with soil microbial properties in Artemisia sacrorum communities in the loess hilly region

Abstract: Artemisia sacrorum communities with different growth years were selected to analyse soil nutrient characteristics, the variation in soil microbial properties, and their relationships in the loess hilly region. The results showed that with an

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that afforestation not only improves the soil environment (Zhao et al, 2017), including soil nutrients, moisture, and structure (Deng, Kim, Peng, & Shangguan, 2018; Xiao et al, 2017; Zhang, An, Cai, Guo, & Xiao, 2017; Zhu, Deng, Zhang, & Shangguan, 2016) of plants, but also significantly influences plant diversity (Abella, 2010; Díaz‐García, Pineda, López‐Barrera, & Moreno, 2017; Laughlin et al, 2017; Xiao et al, 2017) and ecosystem productivity (Uthappa et al, 2018). Many studies have also reported that soil nutrients such as nitrogen and phosphorus are important factors affecting vegetation coverage, plant community composition, and plant diversity (Chen et al, 2017; Liu, Xing, & Yang, 2017; Sanaei, Ali, & Chahouki, 2018; Seabloom et al, 2017; Song, Liu, Wu, Gao, & Hao, 2018; Wei et al, 2017; Zhu, Tang, Shangguan, & Deng, 2018). Competition for soil resources, especially nitrogen, leads to spatial heterogeneity in communities and there is a relationship between competition and coexistence within plant communities (Tilman, 1982, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that afforestation not only improves the soil environment (Zhao et al, 2017), including soil nutrients, moisture, and structure (Deng, Kim, Peng, & Shangguan, 2018; Xiao et al, 2017; Zhang, An, Cai, Guo, & Xiao, 2017; Zhu, Deng, Zhang, & Shangguan, 2016) of plants, but also significantly influences plant diversity (Abella, 2010; Díaz‐García, Pineda, López‐Barrera, & Moreno, 2017; Laughlin et al, 2017; Xiao et al, 2017) and ecosystem productivity (Uthappa et al, 2018). Many studies have also reported that soil nutrients such as nitrogen and phosphorus are important factors affecting vegetation coverage, plant community composition, and plant diversity (Chen et al, 2017; Liu, Xing, & Yang, 2017; Sanaei, Ali, & Chahouki, 2018; Seabloom et al, 2017; Song, Liu, Wu, Gao, & Hao, 2018; Wei et al, 2017; Zhu, Tang, Shangguan, & Deng, 2018). Competition for soil resources, especially nitrogen, leads to spatial heterogeneity in communities and there is a relationship between competition and coexistence within plant communities (Tilman, 1982, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The topography of the loess hilly region is dominated by sloping land, many of which have great gradient and loose soil structure, resulting in serious soil erosion (Song et al, 2018;Yang and Lu, 2018). In addition, there is little irrigation in the loess hilly region, and most of the crop growth depends on natural precipitation (Qin et al, 2014;Gao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Crop residue and stubble retention are core features of conservation tillage, although the benefits of stubble retention are regionally variable, depending on both agro-climatic and socioeconomic factors [3] . Positive effects of stubble retention on agricultural sustainability include increasing SOC, soil water retention and nutrient cycling together with decreasing soil loss [3][4][5][6] . In addition to stubble retention after harvesting, conservation tillage also includes no tillage (NT) and spring ridge tillage (SRT), NT refers to nothing will be done to the field before sowing, SRT refers to ridging the field before sowing, NT and SRT are widely utilized in China [7] .…”
Section: Introduction mentioning
confidence: 99%